Parentality and children’s self-esteem: A revision over the importance of family strengthening for the positive development of children - Vargas Rubilar, Jael Alejandra (2011)
Positive self-esteem promotes health and protects against dysfunctionality, emerging as an important factor of resilience. Its development in early stages favors a functional adaptation to the environment and prevents emotional discomfort in the long term. Since literature states that a family is a key factor for the creation of children’s self esteem, this research will review some family conditions that can affect the personal assessment of the children, highlighting the necessity of creating psychosocial approaches for the creation of healthy family environments, optimizing the parental competences and strengthening the affective bond between parents and children.